A 19-Year-Old-Woman With Backache, Hemoptysis, and Hypereosinophilia - YILDIZELİ, BEDRETTİN (ELSEVIER, 2021)
CASE PRESENTATION: A 19-year-old woman presented to our ED with complaints of backache and massive hemoptysis. Her medical history included acute dyspnea that developed within hours caused by angioneurotic edema 6 months earlier. Two days later, she was given thrombolytic treatment because of massive pulmonary thromboembolism. She had been given methylprednisolone 4 mg and tinzaparin sodium 0.7 mL subcutaneously and was still under treatment on the current admission. She had no history of smoking, alcohol, or oral contraceptive use, surgery, trauma, recent travel, clotting disorders, or familial diseases.